Establishment of a genetic transformation system for cordycipitoid fungus Cordyceps chanhua - Cai, Ruihang; Xiao, Yu; Xing, Jiajia; Yu, Kongjian; Li, Xiaola; Chai, Yiqiu (Frontiers in Microbiology, 2024)
Cordyceps chanhua is a well-known edible and medicinal mushroom with a long history of use in China, and it contains a variety of secondary metabolites with interesting bioactive ingredients. However, recent researches have mainly focused on cultivation conditions, secondary metabolite compositions and pharmacological activities of C. chanhua, the lack of an efficient and stable genetic transformation system has largely limited further research on the relationship between secondary metabolites and biosynthetic gene clusters in C. chanhua. In this study, single-factor experiments were used to compare the effects of different osmotic stabilizers, enzyme concentrations and enzyme digestion times on protoplast yield, and we found that the highest yield of 5.53 × 108 protoplasts/mL was obtained with 0.7 M mannitol, 6 mg/mL snail enzyme and 4 h of enzyme digestion time, and the regeneration rate of protoplasts was up to approximately 30% using 0.7 M mannitol as an osmotic stabilizer. On this basis, a PEG-mediated genetic transformation system of C. chanhua was successfully established for the first time, which lays the foundation for further genetic transformation of C. chanhua.